BOX MODEL AIR TAWAR, SALINITAS DAN ZAT HARA DI DELTA MAHAKAM KALIMANTAN TIMUR - Hadikusumah, Hadikusumah; Simanjuntak, Marojahan (Makara Journal of Science, 2011)
Box Model of Freshwater, Salinity and Nutrient in the Delta Mahakam East Kalimantan. Research has been conducted in the southern part of the Mahakam Delta, East Kalimantan. Method of measuring temperature, salinity, light transmission and turbidity by using CTD model 603 SBE and current measurement and bathymetry by using ADCP model RDI. Measurement parameters on the nutrient chemistry are based of water samples taken using Nansen bottles from two depths. The purpose of this study to determine the mechanism of freshwater, salinity and nutrient transport from the land of the Mahakam River which interact with seawater by using box models. The results illustrate that the vertical distribution of salinity in the Mahakam Delta has obtained a high stratification, where the freshwater salinity 12.30 psu at the surface of a river flowing toward the sea, and seawater of high salinity 30.07 psu flowing in the direction river under the surface that are separated by a layer of mixture. Freshwater budget of the sea (VSurf) obtained for 0,0306 x 109 m3 day-1, and the sea water salinity budget is going into the bottom layer system (VDeep.SOcn-d) obtained for 20,727 x 109 psu day-1. While time dilution (τSyst) obtained for 0.245 day-1 or 5.87 hours. Nutrient budget in the surface layer obtained by the system is autotrophic while in layers near the bottom tend to be heterotrophic.